2015
DOI: 10.3835/plantgenome2014.10.0077
|View full text |Cite
|
Sign up to set email alerts
|

Phytic Acid and Inorganic Phosphate Composition in Soybean Lines with Independent IPK1 Mutations

Abstract: Soybean seeds contain a large amount of P, which is stored as phytic acid (PA). Phytic acid is indigestible by nonruminant livestock and considered an antinutritional factor in soybean meal. Several low PA soybean lines have been discovered, but many of these lines have either minor reductions in PA or inadequate germination and emergence. The reduced PA phenotype of soybean line Gm-lpa-ZC-2 was previously shown to be the result of a mutation in a gene encoding an inositol pentakisphosphate 2-kinase on chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 43 publications
1
20
1
Order By: Relevance
“…In soybean, several mutant populations have been created using various mutagenic agents such as chemical, irradiation, or transposon (Campbell & Stupar, 2016). More recently, fast neutron (FN) mutant populations were utilized to identify and characterize several causative genes or genetic loci for important seed composition phenotypes in soybean such as increased production of vitamin E (Stacey et al ., 2016), sucrose (Dobbels et al ., 2017), stearic acid (Gillman et al ., 2014), reduced seed phytic acid (Vincent et al ., 2015) or altered plant morphology (Bolon et al ., 2011; Hwang et al ., 2015). One advantage of FN mutagenesis is the induction of genetic deletions which can be rapidly identified by comparative genome hybridization (CGH).…”
Section: Introductionmentioning
confidence: 99%
“…In soybean, several mutant populations have been created using various mutagenic agents such as chemical, irradiation, or transposon (Campbell & Stupar, 2016). More recently, fast neutron (FN) mutant populations were utilized to identify and characterize several causative genes or genetic loci for important seed composition phenotypes in soybean such as increased production of vitamin E (Stacey et al ., 2016), sucrose (Dobbels et al ., 2017), stearic acid (Gillman et al ., 2014), reduced seed phytic acid (Vincent et al ., 2015) or altered plant morphology (Bolon et al ., 2011; Hwang et al ., 2015). One advantage of FN mutagenesis is the induction of genetic deletions which can be rapidly identified by comparative genome hybridization (CGH).…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that the peak for fraction 53 represents inositol pentaphosphate (IP5) bound to calcium. It has been reported that in soybean phytic acid contributes 93 % of the total inositol phosphate and IP5 contributes only 3 % (Vincent et al, 2015), while in soy flakes, 14 % of the inositol phosphate is in the form of IP5 (Lehrfeld, 1989). Further studies are needed to identify the peak for fraction 53.…”
Section: Resultsmentioning
confidence: 99%
“…However, when this novel mutation was combined with the mutated IPK1 isoform encoded on chromosome 14 (Glyma14g07880), a drastic reduction in seed phytic acid accumulation was observed. Unlike other low phytic acid mutants in soybean, the double IPK1 mutant showed no significant reductions in germination or field emergence (Vincent et al., ).…”
Section: Community Accessible Soybean Mutant Resourcesmentioning
confidence: 94%